Remote sensing and the mobility of buffalo and cattle in Southern Africa : a review of the key environmental factors and their characterization from Earth observation satellite imagery [poster] - (:unkn) unknown (My University, 2019)
Gordon Research Conference.Movement Ecology of Animals.Animal Movement as a Link Between Ecology, Evolution and Behavior, Barga, ITA, 03-/03/2019 - 08/03/2019
Keywords: African Research